Evaluación farmacognóstica y preclínica de la actividad laxante en la semilla de linaza (Linum usitatissimum) - Zhañay Armijos, Mercedes C (2014)
Flaxseed is flat and oval with a pointed edge, which has a toasted and chewy texture with pleasant nutty flavor from the therapeutic point of view is attributed various properties and including laxative action. This research work has as main goal, pharmacognostic mind and preclinically evaluates the laxative activity in seeds of Linseed (Linum usitatissimum). The research was conducted at the Laboratory of Pharmacy Pilot Plant, Laboratory and Vivarium Research School of Chemical Sciences and Health, Technical University of Machala.